Ocular Ischemic Syndrome as A Cause of Chronic Visual Loss: Case Report and Review Literature - คงสาคร, นฤมล; แสงวณิช, ศันสนีย์ (Journal of Thai Stroke Society, 2019)
We reported a 68-year-old man, known case of hypertension, diabetes mellitus type 2, hyperlipidemia, ex-smoker and laryngeal cancer status post total laryngectomy and radiation therapy 14 years ago, presented with progressive bilateral visual loss for 1 year. Eyes examinations and vascular investigations are compatible with the findings of ocular ischemic syndrome that caused by carotid occlusive disease of bilateral carotid system.